RETRACTED: Clinico-demographic and survival profile of people living with HIV on antiretroviral treatment - Riyaz Ahamed Shaik; Sharan K. Holyachi; Mohammad S. Ahmad; Mohammed Miraj; Mansour Alzahrani; Ritu Kumar Ahmad; Bader A. Almehmadi; Mohammed Zaid Aljulifi; Meshari A. Alzahrani; Mashael B. Alharbi; Mohammed Muzammil Ahmed (Frontiers Media S.A., 2023)
ObjectiveTo assess the demographic, clinical, and survival profile of people living with HIV.MethodsA retrospective cohort study was conducted among patients enrolled at a single antiretroviral therapy center in North Karnataka. A total of 11,099 were recruited from April 2007 to January 2020, out of which 3,676 were excluded and the final 7,423 entries were subjected to analysis. The outcome of interest was the time to death in months of people living with HIV on antiretroviral therapy (ART). The clinical and demographic characteristics were examined as potential risk factors for survival analysis. To investigate the factors that influence the mortality of patients using ART, univariate and multivariate Cox regression were performed. Hazard ratio (HR), 95% confidence interval (CI), and p-values were presented to show the significance. The log-rank test was used to determine the significance of the Kaplan-Meier survival curve.ResultsOut of 7,423 HIV-positive people, majority were female (51.4%), heterosexual typology (89.2%), and in the age group 31-45 years (45.5%). The risk of death in male patients was 1.24 times higher (95% CI: 1.14-1.35) than female patients. Patients with age >45 were 1.67 times more likely to die than patients ≤30 (95% CI: 1.50-1.91). In the multivariable analysis, the hazards of mortality increased by 3.11 times (95% CI: 2.09-2.79) in patients with baseline CD4 count ≤50 as compared to those who had baseline CD4 count >200. The risk of death in patients who were diagnosed with TB was 1.30 times more (95% CI: 1.19-1.42) than in those who did not have TB. The survival probabilities at 3 and 90 months were more in female patients (93%, 70%) compared with male patients (89, 54%), respectively.ConclusionThis study proved that age, sex, baseline CD4 count, and tuberculosis (TB) status act as risk factors for mortality among people with HIV. Prevention strategies, control measures, and program planning should be done based on the sociodemographic determinants of mortality.